PENERAPAN ALGORITMA LEAST SQUARE DALAM MEMPREDIKSI PENJUALAN GAS LPG NON SUBSIDI - Hernandi, Gelen Betanio; Erlin Elisa (LPPM Universitas Putera Batam, 2024)
LPG gas is one of the most needed fuel sources today, especially for household cooking needs. The need for this type of fuel increases every day, month, even year in accordance with the addition of members in the family itself. The increasing consumption of LPG gas in the community cannot be separated from the need for LPG gas which is expected to continue to increase, as well as the country's population which is growing at a rate of 1.49% annually. PT Dinamika Purnakarya Persada is an authorized agent of non-subsidized LPG gas in Batam City. Where this PT is engaged in the distribution and sale of Bright Gas Non Subsidized. From the results of a survey conducted previously, the problem so far is when the LPG gas situation is scarce, making it difficult to meet customer demand. As a result, sales at PT Dinamika Purnakarya Persada decreased, causing disappointment to customers. To overcome the above problems, the authors will apply the Least Square Method as a strategy commonly used to predict sales. This approach is a system in the form of periodic or time series data, in which some historical sales data is needed to estimate sales results in the following years. By looking at historical data, sales transactions are in the months of January to December 2024 for 50KG gas cylinders, as well as 12KG cylinders, while for 5.5KG gas cylinders are in January 2024.